Ghost protein damage by peroxynitrite and its protection by melatonin - P. Di Mascio; B. Dewez; C.R.S. Garcia (Brazilian Journal of Medical and Biological Research, 2000)
We have studied the effect of peroxynitrite (ONOO-) on the membrane cytoskeleton of red blood cells and its protection by melatonin. Analysis of the protein fraction of the preparation by SDS-PAGE revealed a dose-dependent (0-600 µM ONOO-) disappearance at pH 7.4 of the main proteins: spectrin, band 3, and actin, with the concomitant formation of high-molecular weight aggregates resistant to reduction by ß-mercaptoethanol (2%) at room temperature for 20 min. These aggregates were not solubilized by 8 M urea. Incubation of the membrane cytoskeleton with ONOO- was characterized by a marked depletion of free sulfhydryl groups (50% at 250 µM ONOO-). However, a lack of effect of ß-mercaptoethanol suggests that, under our conditions, aggregate formation is not mediated only by sulfhydryl oxidation. The lack of a protective effect of the metal chelator diethylenetriaminepentaacetic acid confirmed that ONOO--induced oxidative damage does not occur only by a transition metal-dependent mechanism. However, we demonstrated a strong protection against cytoskeletal alterations by desferrioxamine, which has been described as a direct scavenger of the protonated form of peroxynitrite. Desferrioxamine (0.5 mM) also inhibited the loss of tryptophan fluorescence observed when the ghosts were treated with ONOO-. Glutathione, cysteine, and Trolox® (1 mM), but not mannitol (100 mM), were able to protect the proteins against the effect of ONOO- in a dose-dependent manner. Melatonin (0-1 mM) was especially efficient in reducing the loss of spectrin proteins when treated with ONOO- (90% at 500 µM melatonin). Our findings show that the cytoskeleton, and in particular spectrin, is a sensitive target for ONOO-. Specific antioxidants can protect against such alterations, which could seriously impair cell dynamics and generate morphological changes.